Comparative Study of Achievement and Participation in the National Science Olympiad: A Case Study of Java and Non-Java Regions - Falentino, Charlos; Dinurrohmah, Syayidah; Sulaeman, Nurul Fitriyah; Nuryadin, Atin (Jurnal Literasi Pendidikan Fisika (JLPF), 2024)
The Merdeka Curriculum provides opportunities for all Indonesian students to explore their talents, one of which is through the National Science Olympiad (OSN). This study aims to analyze student participation and achievement in OSN across regions in Indonesia. This research was conducted using a quantitative approach and cluster random sampling technique. Respondent categories were divided based on student domicile areas: Java and non-Java. The participation and achievement of students in both regions showed that students domiciled in Java Island still dominate participation and achievement in OSN. The study also found that school facilities, costs, and lack of support from teachers and parents are the main obstacles for students outside Java. The impact of OSN is also very beneficial, especially in supporting students' studies and careers, as well as increasing the chances of better educational opportunities in the future. These results provide essential information on equitable improvements in support and access for students and schools in all parts of Indonesia to participate in the OSN.